Comparative metabolomics reveals streptophenazines with anti-methicillin-resistant Staphylococcus aureus activity derived from Streptomyces albovinaceus strain WA10-1-8 isolated from Periplaneta americana - Liuchong Zhu; Dan Huang; Jinli Tan; Jiaxuan Huang; Ruyu Zhang; Jingyang Liao; Jie Wang; Xiaobao Jin (BMC Microbiology)
Abstract Background Streptophenazines, a class of phenazine compounds with a variety of alkyl side chains and activity against methicillin-resistant Staphylococcus aureus (MRSA), are mainly derived from soil or marine microbial secondary metabolites. However, the discovered phenazine compounds still do not meet the needs of the development of anti-MRSA lead compounds. Here, we examined secondary metabolites of Streptomyces albovinaceus WA10-1-8 isolated from Periplaneta americana, for streptophenazines with anti-MRSA activity. Results In this study, a guidance method combining high-performance liquid chromatography-ultraviolet (HPLC-UV) with molecular networking analysis was used to isolate and identify a series of streptophenazines (A–T) from S. albovinaceus WA10-1-8. Among them, a new streptophenazine containing a dihydroxyalkyl chain structure named streptophenazine T was isolated and identified for the first time. The results of bioactivity assays showed that streptophenazine T had anti-MRSA activity with a minimum inhibitory concentration (MIC) of 150.23 µM, while the MICs of streptophenazine A, B, G, and F were 37.74-146.12 µM. Conclusions This study was the first to report multiple streptophenazine compounds with anti-MRSA activity expressed by Streptomyces isolated from insect niches. These results provided a valuable reference for future exploration of new streptophenazine compounds with activity against drug-resistant bacteria.